Putting a financial accounting and a health economic perspective face to face to inform public health management decision-making - Candio, Paolo; Francesconi, Andrea; Collini, Paolo (Mecosan - Management ed Economia Sanitaria - Open Access, 2025)
Evidence-based decision-making serves as a fundamental principle in public health management, particularly in resource allocation. Various economic frameworks have been devised to support these decisions, each grounded in distinct philosophies and objective functions. Nonetheless, public health managers increasingly face the complex task of balancing the needs and perspectives of diverse stakeholders, often leading to conflicting interests, significantly hindering optimal managerial decision-making and policy implementation. Indeed, depending on what benefits are considered and their relative value, choice of intervention may change. However, to date no empirical study has analytically examined this issue. This paper addresses this gap by applying a break-even analysis approach and utilizing a real-world case study in stroke treatment. We illustrate how patient volume requirements can vary significantly based on whether a financial accounting or a health economic perspective on the benefits of the intervention is adopted.